PENAFSIRAN AYAT-AYAT PERBUATAN MANUSIA: (Telaah Kitab Tafsir Al-Kasysyaf Karya al-Zamakhsary) - Yasser Muda Lubis; Muhammad Jihad (Universitas PTIQ Jakarta, 2022)
Humans are faced with various life choices. Choosing, wanting and living these choices is a common thing to do. However, whether human choices, wills and actions are sourced from themselves or are they all determined by the destiny of God, the creator of everything. This phrase will get different answers from some theological groups. Each has strong arguments and refutation of arguments that contradict each other. Of these groups, one of the most phenomenal is the rationalist Mu'tazilah group. Al-Zamakhsyari was one of the great figures of the Mu'tazilah. Tafsir Al-Kasysyaf is the work of al-Zamakhsyari who has contributed greatly to the understandings of the Mu'tazilah, including their understanding of the concept of human action. This area will be discussed in this article. The author takes several crucial verses about the concept of human action, then analyzes al-Zamakhsyari's interpretation of these verses followed by comments or opinions of the interpreters after al-Zamakhsyari's life. Al-Zamakhsyari's efforts in defending his ideology through the interpretation of the verses of the Qur'an become an interesting study that will be discussed in this paper. Al-Zamakhsyari does this by making additions or interpretations that can attract the editor of the verse to agree with his ideology.